1996
DOI: 10.1016/s0092-8674(00)80085-9
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Apoptotic Program in Cell-Free Extracts: Requirement for dATP and Cytochrome c

Abstract: A cell-free system based on cytosols of normally growing cells is established that reproduces aspects of the apoptotic program in vitro. The apoptotic program is initiated by addition of dATP. Fractionation of cytosol yielded a 15 kDa protein that is required for in vitro apoptosis. The absorption spectrum and protein sequence revealed that this protein is cytochrome c. Elimination of cytochrome c from cytosol by immunodepletion, or inclusion of sucrose to stabilize mitochondria during cytosol preparation, dim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

93
3,223
7
41

Year Published

1998
1998
2002
2002

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 4,769 publications
(3,364 citation statements)
references
References 44 publications
93
3,223
7
41
Order By: Relevance
“…Whereas other studies have demonstrated that release of cyt c from mitochondria induces a cas-3-mediated apoptotic cascade (Li et al, 1997;Liu et al, 1996;Zou et al, 1997), we asked if heat-shock treatment inhibits cyt cmediated activation of cas-3. As demonstrated previously for other cell types, expression of Hsp27 was induced in 293T cells at 6 ± 8 h after mild heat shock (Figure 1a).…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…Whereas other studies have demonstrated that release of cyt c from mitochondria induces a cas-3-mediated apoptotic cascade (Li et al, 1997;Liu et al, 1996;Zou et al, 1997), we asked if heat-shock treatment inhibits cyt cmediated activation of cas-3. As demonstrated previously for other cell types, expression of Hsp27 was induced in 293T cells at 6 ± 8 h after mild heat shock (Figure 1a).…”
Section: Resultsmentioning
confidence: 97%
“…Previous studies have demonstrated that release of cyt c from mitochondria to cytosol is an important step in inducing cas-3-mediated apoptosis (Li et al, 1997;Liu et al, 1996;Zou et al, 1997). To assess whether Hsp27 functions upstream or downstream to cyt c release from mitochondria, L929/pRc and L929/Hsp27 cells were treated with various agents, such as methylmethane sulphonate (MMS), 1-b-D-arabinofuranosyl-cytosine (ara-C) or staurosporine (STSP), that are known to cause the release of mitochondrial cyt c (Kharbanda et al, 1997a), and cytosols were analysed by immunoblotting (IB) with anti-cyt c. The results demonstrate that MMS treatment of both L929/pRc and L929/Hsp27 cells is associated with the release of cyt c ( Figure 3a, upper panel).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In certain situations, death stimuli induce an increase in the permeability of the outer mitochondrial membrane that releases apoptosis inducers, such as cytochrome c [39] and apoptosis-inducing factor (AIF) [40]. In our study, the ΔΨm was quantified by the flow cytometric analysis of JC-1-stained cells.…”
Section: Discussionmentioning
confidence: 99%